Lymph node metastases develop through a wider evolutionary bottleneck than distant metastases - Reiter, Johannes G.; Hung, Wei-Ting; Lee, I-Hsiu; Nagpal, Shriya; Giunta, Peter; Degner, Sebastian; Liu, Gang; Wassenaar, Emma C. E.; Jeck, William R.; Taylor, Martin S.; Farahani, Alexander A.; Marble, Hetal D.; et al. (Nature genetics, 2020)
Genetic diversity among metastases is poorly understood but contains important information about disease evolution at secondary sites. Here we investigate inter- and intra-lesion heterogeneity for two types of metastases that associate with different clinical outcomes: lymph node and distant organ metastases in human colorectal cancer. We develop a rigorous mathematical framework for quantifying metastatic phylogenetic diversity. Distant metastases are typically monophyletic and genetically similar to each other. Lymph node metastases, in contrast, display high levels of inter-lesion diversity. We validate these findings by analyzing 317 multi-region biopsies from an independent cohort of 20 patients. We further demonstrate higher levels of intra-lesion heterogeneity in lymph node than in distant metastases. Our results show that fewer primary tumor lineages seed distant metastases than lymph node metastases, indicating that the two sites are subject to different levels of selection. Thus, lymph node and distant metastases develop through fundamentally different evolutionary mechanisms. Analysis of metastases using a mathematical framework and multi-region sampling data shows that lymph node metastases have higher levels of intratumor heterogeneity than distant metastases, and that these form via different evolutionary mechanisms.